Динаміка запасу та енергетичного потенціалу підстилки лісових екосистем за період вегетації 2007 р. (на прикладі модельних ділянок заказника «Лісники», м. Київ) - Дідух, Я.П.; Гаврилов, С.О. (Український фітоценологічний збірник, 2007)
Исследования проведены в апреле–октябре на мониторинговых ключевых участках двух ассоциаций лиственных (Ficario-Fraxinetum; all. Alno-Ulmion) и хвойных (all. Chamaecytiso-Pinion) лесов, возраст древостоя которых превышает 100 лет. Определяли ежемесячные запасы подстилки, что позволило оценить динамику ее накопления и рассчитать соответствующие энергетические показатели. Установлено, что в неморальных лесах эти показатели характеризуются более значительными сезонными колебаниями, чем в хвойных, а интенсивность накопления подстилки в лиственных лесах в два раза выше, чем в хвойных. Сравнивая интенсивность накопления и разложения подстилки рассчитано, что устойчивость хвойных лесов в два раза превышает таковую лиственных. Research has been conducted during April-October based on the key monitored plots that were set up in two associations of deciduous (Ficario- Fraxinetum; all. Alno- Ulmion) and coniferous (all. Chamaecytiso-Pinion) forests with the treestand over a 100 years old. Monthly estimations of the amount of the debris layer enabled to evaluate dynamics of its accumulation and to calculate corresponding indicators of energy. It has been established that seasonal fluctuations of these indicators are significantly greater in nemoral forests as compared to the coniferous forests. Intensity of the debris layer accumulation in the deciduous forests was two times that of the coniferous forests. Based on the comparison of the intensity of the debris accumulation and degradation, sustainability of coniferous forests was calculated to be twice that of deciduous forests.